Lactic Acid Production From Broken Rice Via Fermentation Process - Shuhada Baharuddin, Nur (Pusat Pengajian Teknologi Industri, 2020)
One of the consequences of industrial food production activities is the generation of high volumes of waste, whose disposal can be problematic, since it occupies large spaces and when poorly managed can pose environmental and health risks for the population. The rice industry is an important activity and generates large quantities of waste. The main solid waste generated in the rice production cycle is broken rice. Broken rice refers to the fragments of rice grain obtained by milling and separated after the polishing phase. It has the same chemical composition as white rice and its most important components are carbohydrates. The aim of this research is to investigate the optimum condition and potential of utilizing fermented broken rice to the production of lactic acid using different strain of bacteria culture. Different process parameters such as pH of the medium, temperature, agitation speed and substrate concentration were used to study the optimum condition. Then, the growth kinetics and modelling of lactic acid production from broken rice were studied in a batch system. From the screening process, the highest lactic acid concentration of 5.24 g/L was obtained from Lactobacillus acidophilus strain at pH 7, Temperature 35ºC, 150 rpm agitation speed and the substrate used was 50 g/L. Unstructured models were proposed using the logistic equation for growth, the Luedeking-Piret equation for lactic acid production and modified Leudeking-Piret model for substrate consumption. The parameters estimation for the experiment data for batch fermentation µmax = 0.2582 h-1, XO = 2.281 g/L, Xm = 8.60 g/L, Yx/s = 0.200 g/g, Yp/s = 0.74 g/g and maintenance coefficient (ms) = 0.017 g glucose g−1 biomass h−1. From the Leudeking – Piret equations the α, ß value obtained were 0.179 and 0.014 respectively. Excellent significant R2 values of 0.8452, 0.9245, and 0.9669 were observed for biomass, lactic acid production and substrate consumption, respectively. The values indicated that the model used was able to interpret the fermentation kinetic in the batch fermentation. The feasibility study shown broken rice having high potential to be a new sustainable source for the lactic acid production.